Sternohyoideus‐sternothyroideus muscle flap to reconstruct oronasal fistulas due to maxillary cancer in four dogs. Issue 2 (13th December 2022) - Ciepluch, Brittany J.; Séguin, Bernard; Worley, Deanna
Abstract: Objective: To describe the repair of oronasal fistulas in dogs treated for maxillary cancer, with a novel sternohyoideus‐sternothyroideus muscle flap, and to report the outcome. Animals: Client‐owned dogs ( n = 4) with oronasal fistulas related to cancer. Study design: Short case series. Methods: Maxillary defects were caused by tissue destruction by the tumor and tumor response to radiation therapy in two cases and a complication of caudal maxillectomy in two cases, one of which had neoadjuvant radiation therapy. All tumors were >4 cm at the level of the maxilla. Flaps were harvested by transecting the ipsilateral sternothyroideus and sternohyoideus muscles from their origin at the manubrium and costal cartilage. The muscles were rotated around the base of the cranial thyroid artery and tunneled subcutaneously in the neck and through an incision in the caudodorsal aspect of the oral cavity. The muscle flap was sutured to the edges of the oronasal fistula. Results: The flap reached as far rostral as the level of the first premolar without tension. All dogs had clinical signs that improved postoperatively. All dogs had partial dehiscence of the flap. Conclusion: This flap was associated with a high rate of complications; however, all flaps were used in challenging cases. Clinical signs related to oronasal fistula were improved in all dogs in this case series.